Examining the factors associated with the well-being of children who have a sibling with a chronic health condition: a literature synthesis - DeGroot, Aria (My University, 2026)
This literature analysis examines factors associated with well-being among children with a sibling who has a chronic health condition, drawing on recent qualitative, quantitative, and mixed-methods research. Findings consistently demonstrate elevated risks for emotional distress, anxiety, and behavioural difficulties among healthy siblings, alongside evidence of resilience and positive growth. From this research, three main factors emerge: family environments, individual coping strategies, and illness severity regarding the degree of impact of illness on the healthy sibling. These factors interact in meaningful ways, influencing how healthy siblings experience chronic illness.
Keywords: childhood illness; family adjustment; siblings